Organic acids and food preservation - Theron, Maria M. (Taylor & Francis, 2011)
The demand for nutritious foods that are free of pathogens as well as harmful additives is growing daily. Because of their natural occurrence in food and because they inhibit the growth of most microorganisms, organic acids are increasingly used in food preservation. "Organic Acids and Food" provides easily accessible operating procedures, new directives, and possible alternative methods or solutions to problems. Each chapter addresses an important aspect of organic acids, including composition, application, production, resistance, as well as the advantages and disadvantages of prese.
Keywords: Food -- Preservation.; Organic acids.; elektronické knihy; electronic books